Juridical Implications of Differences in Witness Testimony between Trial and Investigation Report - Isnawanti Isnawanti; A Muin Fahmal; Ilham Abbas (Fakultas Hukum, Universitas Muslim Indonesia, 2026)
Differences in witness testimony between the Investigation Report (Berita Acara Pemeriksaan/BAP) at the investigation stage and statements delivered during trial are a phenomenon that frequently occurs in criminal justice practice in Indonesia. This study aims to analyze the juridical implications as well as the factors influencing such differences from the perspective of criminal procedural law. The research method employed is empirical juridical with a qualitative approach through normative study and field data. The findings indicate that discrepancies in witness testimony do not always reflect inconsistencies that weaken evidentiary value; rather, they may be influenced by internal witness factors, external situational factors, and procedural factors within the examination process. The Criminal Procedure Code (KUHAP) places testimony delivered in court as evidence with primary probative value, while the BAP functions as a supporting instrument to assess consistency. Therefore, judges must evaluate differences contextually by considering the substance of facts, their correlation with other evidence, and the principle of seeking material truth. Strengthening the professionalism of law enforcement officers and enhancing witness protection are essential to minimize substantive discrepancies and maintain the quality of the evidentiary process.